High-Intensity Interval Cycle Ergometer Training in Parkinson's Disease: Protocol for Identifying Individual Response Patterns Using a Single-Subject Research Design - van Wegen, Erwin E. H.; Hirsch, Mark A.; van de Berg, Wilma D. J.; Vriend, Chris; Rietberg, Marc B.; Newman, Mark A.; Vanbellingen, Tim; van den Heuvel, Odile A. (Frontiers in Neurology, 2020)
Background: People with Parkinson's disease (PD) experience not only motor problems but also non-motor problems that seriously impede their daily functioning and quality of life. The current pharmacologic treatment of PD is symptomatic and alternative rehabilitation treatments are needed, which preferably also have a disease-modifying effect and promote neuroplasticity. Recent studies suggest that high intensity interval training (HIIT) is promising for promoting neuroplasticity in human PD, with short training time and reduced burden. Biomarkers for neuroplasticity such as brain-derived neurotrophic factor (BDNF) and neurodegeneration (including neurofilament NfL and α-synuclein) may play a role but their response to HIIT is not well investigated. Objectives: 1) to study the effects of 4 weeks of HIIT compared to 4 weeks of ContinuousAerobicExercise on motor and non-motor outcomes of PD; 2) to investigate the association between blood biomarkers levels for neuroplasticity and neurodegeneration and motor and non-motor performance. Study Design: Single Subject Research Design with alternating treatment setup (ABACA) and frequent repeated measurements. Each participant receives different intervention conditions (B / C) interspersed with baseline periods (A, i.e. ABACA or ACABA) and frequent repeated assessment of outcome measures are done to quantify within-subject, individual response patterns with sufficient power for data analysis. Blood samples will be collected once a week in the baseline and training phases (A1,B/C) and once every 2 weeks in the washout phases (A2, A3). Intervention: Four subjects with PD on stable dopaminergic medication, two in Hoehn-Yahr stage 1-2 and two in Hoehn-Yahr stage 2.5-3 will follow an ABACA or ACABA schedule, consisting of blocks with 30-minute sessions of ‘B’ (HIIT) or 50-minute sessions of ‘C’ (CAE) 3x / week for 4 weeks, separated by baseline ‘A’ periods of 8 weeks for a total duration of 28 weeks. Outcome measures: Outcome measures include disease status (UPDRS), blood biomarkers (BDNF, Nfl, α-synuclein), and measures for functional mobility (including an activity tracker), Activities of Daily Living, as well as cognition, mood, biorhythm (sleeping problems) and Quality of life. Data analysis: Visual analysis of trends in level, slope and variability in response patterns, confirmed by longitudinal regression analysis with phase (ABACA) as independent variable.